Experience with Tetanus in a Tertiary Care Hospital in Sudan: A Retrospective Review - Mumen Abdalazim Dafallah; Esraa Ahmed Ragab; Omer Ali Mohamed Ahmed Elawad (Emergency Medicine International)
Introduction. Tetanus is still a major health issue, especially in rural areas, and is associated with high morbidity and mortality rate. This study was conducted to describe the pattern of presentation and treatment outcome among adult patients infected with tetanus in our environment. Materials and Methods. This is a descriptive retrospective hospital-based study conducted in Wad Medani teaching hospital, central Sudan. A total of thirty-one patients were enrolled in this study in the period between January 2018 and December 2020. Results. Thirty-one patients were infected with tetanus during the study period. They were 23 (74.2%) males and 8 (25.8%) females with a male-to-female ratio of 2.875 : 1. Their ages ranged from 20 to 70 years, and most of them (48.4%) were free workers. Acute injuries were the most common portal of entry (64.51%), and commonly involved the lower limbs (48.38%). Lock jaw (54.8%), muscle spasm (51.6%), and neck pain and stiffness (45.2%) were the most common presentation. Supportive measures along with surgical toilet and debridement, human tetanus immunoglobulin, antibiotics, and muscle relaxants were initiated in all patients. The most common antibiotics used were Penicillin V and Ceftriaxone. A muscle relaxant was administered to aid in relieving the spasms. Complication rate was 61.29% and included pulmonary and cardiovascular complications. Fifteen patients died accounting for an overall mortality rate of 48.4%. Conclusions. Tetanus remains a disease with high morbidity and mortality. The unknown/incomplete vaccination status among study participants, inadequate management, and lack of equipped resources lead to a devastating outcome as in Sudan.